Bahasa Arab sebagai Identitas Budaya Sekolah Islam: Kajian Antropolinguistik terhadap Interaksi Guru–Murid - Aslamiyah, Suaibah; Suri, Nursukma; Safira, Raihana; Rawi, Shita Umma (UPA Bahasa Universitas Tidar And HISKI Kedu, 2025)
This study aims to examine the role of Arabic as an indicator of cultural identity in the context of Islamic schools through an anthropolinguistic perspective. Starting from the phenomenon of the use of Arabic in daily interactions between teachers and students such as greetings, commands, and religious expressions this study examines how these linguistic practices reflect the values, ideologies, and social order in Islamic education. Data were obtained through observations of classroom interactions and informal communication within the school environment, then analyzed by emphasizing forms of speech such as commands, polite greetings, and student responses that are imbued with cultural meaning. The findings indicate that Arabic is not merely a means of educational communication, but also an institutional symbol that shapes religious customs, discipline, and hierarchies of power in Islamic schools. The practice of using Arabic serves as a means of reproducing Islamic values and an effort to strengthen the cultural identity of institutions in the era of educational modernization. These results contribute theoretically to the development of anthropolinguistic studies in Islamic education and provide empirical evidence of language as a cultural constructor and identity marker in the educational field.